COVID-19 and Cancer Patients - Patel, Rajvi (Cancer Med J, 2020)
COVID-19 has now been declared a global pandemic with evolving incidence rates and fatalities. It is important to identify vulnerable populations who will be impacted most by this pandemic leading to higher mortality rates compared to the general healthy population. Although older patients and patients with co-morbidities fall into this vulnerable group, patients with hematologic and oncologic malignancies on active cytotoxic treatments are at even greater risk as they are both myelosuppressed and immunosuppressed. In addition to following the universal guidelines recommended by the Centers for Disease Control (CDC), it is important to also institute guidelines for cancer centers to help protect this vulnerable population. We review the current data, risks, and recommendations for COVID-19 in cancer patients.